KONSEP PENDIDIKAN ISLAM DAN TOLERANSI DALAM FILM SANG PENCERAH - Muhammad Girindrawardana Agus Putra; Muhammad Nur Salim (Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang, 2020)
The context of the title of this research is how important it is to pay attention and examine content in films that are worth watching, especially films with religious genre. In the film the enlightener, there is a discussion of the concepts of education and tolerance. From the understanding and content of the film, viewers and educators can emulate the struggles of previous scholars and heroes. Moreover, the film hints at accepting many useful new things and an open attitude towards the problems of the times so that Muslims can respond to the times. The focus of this research is divided into three: (1) What is the concept of Islamic education in the film â€œSang Pencerahâ€?. (2) How about tolerance in the film